A composite silicon-carbon material, its preparation method and application

CN122992048APending Publication Date: 2026-10-27ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611479199.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,硅材料在实际应用过程中仍存在明显不足:一方面,硅在充放电过程中会发生较大的体积膨胀和收缩,导致电极结构稳定性下降,并影响活性物质的持续利用;另一方面,硅材料与电解液之间的界面稳定性较差,在长期循环过程中容易造成界面阻抗增加以及电化学性能衰减,仍有进一步改善空间

Benefits of technology

[0031]本发明提供一种复合硅碳材料及其制备方法和应用。该材料通过构建合金化纳米硅核、碳包覆层的复合结构,实现对硅基负极材料结构稳定性和电化学性能的协同优化。其中,合金化纳米硅核采用平均粒径为30-80 nm的纳米硅作为主体,在纳米硅表面形成厚度为8-12 nm的硅-金属复合体,使合金化区域主要分布于颗粒表层,在保持纳米硅高比容量优势的同时,提高颗粒表面的结构稳定性和导电性能。进一步地,在合金化纳米硅核外侧包覆碳包覆层,能够构建连续的电子传输通路,并对纳米硅颗粒提供缓冲和保护作用,减少颗粒间直接接触及界面失稳。通过上述复合结构,在充放电过程中能够有效缓解硅材料体积变化带来的结构损伤,提高颗粒整体稳定性,改善电子传输能力,降低界面副反应,在兼顾高比容量的同时实现优异的综合电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992048A_ABST
    Figure CN122992048A_ABST
Patent Text Reader

Abstract

This invention provides a composite silicon-carbon material, its preparation method, and its applications. The material comprises an alloyed silicon nanonucleus and a carbon coating layer covering at least a portion of the surface of the alloyed silicon nanonucleus; wherein the average particle size of the alloyed silicon nanonucleus is 30-80 nm; the alloyed silicon nanonucleus comprises a silicon core and a silicon-metal composite surrounding the surface of the silicon core, the thickness of the silicon-metal composite being 8-12 nm. When used as a negative electrode material, this material offers both high capacitance and long-cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energy storage technology, and in particular to a composite silicon-carbon material, its preparation method, and its application. Background Technology

[0002] With the rapid development of new energy vehicles, portable electronic devices, and energy storage systems, the demand for high energy density and long cycle life in lithium-ion batteries is constantly increasing. Silicon materials have a high theoretical lithium storage capacity, and silicon resources are abundant and environmentally friendly, therefore they are considered an important candidate for next-generation high-specific-capacity lithium-ion battery anode materials.

[0003] However, silicon materials still have significant shortcomings in practical applications: on the one hand, silicon undergoes significant volume expansion and contraction during charging and discharging, leading to a decrease in electrode structure stability and affecting the continuous utilization of active materials; on the other hand, the interface stability between silicon materials and electrolytes is poor, which can easily cause an increase in interface impedance and a decline in electrochemical performance during long-term cycling, leaving room for further improvement.

[0004] Therefore, how to maintain the high capacitance advantage of silicon-based anode materials while ensuring long-term cycle stability remains a pressing technical problem to be solved. Summary of the Invention

[0005] This invention provides a composite silicon-carbon material with improved conductivity, capacitance and structural stability.

[0006] This invention provides a method for preparing composite silicon-carbon materials, which can obtain materials with improved conductivity, capacitance and structural stability.

[0007] This invention provides an electrode that facilitates continuous contact at the interface and maintains stable cycling.

[0008] This invention provides a battery that, while possessing the advantage of high energy density, also ensures long-term cycle stability.

[0009] This invention provides an electrical device that, while possessing the advantage of high electrical capacity, also takes into account long-term cycle stability.

[0010] In a first aspect, the present invention provides a composite silicon-carbon material, comprising an alloyed nano-silicon core and a carbon coating layer covering at least a portion of the surface of the alloyed nano-silicon core; wherein...

[0011] The average particle size of the alloyed nano-silicon cores is 30-80 nm.

[0012] The alloyed nano-silicon core includes a silicon core and a silicon-metal composite surrounding the surface of the silicon core, wherein the thickness of the silicon-metal composite is 8-12 nm.

[0013] In one possible embodiment, a polymer layer covering at least a portion of the outer surface of the carbon coating layer is further included, the polymer layer having a thickness of 1-10 nm.

[0014] In one possible embodiment, the thickness of the carbon coating layer is 2-10 nm.

[0015] In one possible embodiment, the silicon-metal composite includes a metal element, which includes at least one of Fe, Cu, Ni, Co, Ti, V, and Cr.

[0016] In one possible embodiment, the carbon coating layer is an amorphous carbon layer.

[0017] In one possible embodiment, the polymer layer comprises at least one of carboxymethyl cellulose, polyvinylidene fluoride, and sodium alginate.

[0018] Secondly, the present invention provides a method for preparing the composite silicon-carbon material according to any one of the first aspects.

[0019] The temperature of the plasma arc region is controlled at 1800-2500℃, and a silicon source is continuously introduced during continuous operation for 10-15 minutes to perform nano-sizing treatment and form silicon core raw materials.

[0020] The raw material system, including the silicon core material and the metal source, is alloyed under the condition that the plasma arc temperature is 1800-2500℃ for 15-60 minutes during continuous operation to form the alloyed nano silicon core.

[0021] The alloyed nano-silicon core and carbon source are subjected to carbon coating treatment at 450-550℃ for 10-12 hours to obtain the composite silicon-carbon material.

[0022] In one possible embodiment, after the carbon coating treatment, the product of the carbon coating treatment is further subjected to extrusion mixing with a polymer solution; and then dried at 100-110°C for 8-12 hours to obtain the composite silicon-carbon material.

[0023] In one possible embodiment, the mass ratio of the carbon-coated product to the polymer solution is (95-100):2, and the polymer solution contains 2-2.5 wt.% polymer.

[0024] In one possible embodiment, after the carbon coating treatment, the product of the carbon coating treatment is further subjected to sieve depolymerization treatment before being subjected to the extrusion mixing treatment.

[0025] In one possible embodiment, the mass ratio of silicon in the silicon source to metal in the metal source is (8-10):1.

[0026] In one possible embodiment, the mass of the carbon source is 2-3% of the mass of the alloyed nano-silicon core.

[0027] Thirdly, the present invention provides an electrode comprising the composite silicon-carbon material described in any one of the first aspects of the present invention, or the composite silicon-carbon material obtained by any one of the methods described in the second aspect of the present invention.

[0028] Fourthly, the present invention provides a battery comprising the electrode sheet described in the third aspect of the present invention.

[0029] In one possible embodiment, the battery is a solid-state battery, which includes a solid electrolyte layer. The solid electrolyte material in the solid electrolyte layer includes one of lithium-sulfur-phosphorus-chloride solid electrolyte, lithium sulfide-phosphorus pentasulfide composite sulfide solid electrolyte, and germanium-doped lithium-phosphorus-sulfide solid electrolyte.

[0030] Fifthly, the present invention provides an electrical device including the battery described in the fourth aspect of the present invention.

[0031] This invention provides a composite silicon-carbon material, its preparation method, and its applications. This material achieves synergistic optimization of the structural stability and electrochemical performance of silicon-based anode materials by constructing a composite structure of an alloyed nano-silicon core and a carbon coating layer. The alloyed nano-silicon core uses nano-silicon with an average particle size of 30-80 nm as the main body, forming a silicon-metal composite with a thickness of 8-12 nm on the surface of the nano-silicon. This ensures that the alloyed region is mainly distributed on the particle surface, maintaining the high specific capacity advantage of nano-silicon while improving the structural stability and conductivity of the particle surface. Furthermore, the carbon coating layer on the outside of the alloyed nano-silicon core constructs a continuous electron transport pathway and provides buffering and protection for the nano-silicon particles, reducing direct contact between particles and interfacial instability. Through this composite structure, structural damage caused by volume changes in silicon materials can be effectively mitigated during charge and discharge, improving the overall stability of the particles, enhancing electron transport capability, and reducing interfacial side reactions, achieving excellent comprehensive electrochemical performance while maintaining high specific capacity. Attached Figure Description

[0032] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0033] Figure 1 A schematic cross-sectional structure diagram of the composite silicon-carbon material provided by the present invention;

[0034] Figure 2The SEM characterization spectrum provided by this invention;

[0035] Figure 3 The TEM characterization spectrum provided by this invention;

[0036] Figure 4 The image shown is an EDS spectrum provided by this invention;

[0037] Figure 5 The Si EDS Mapping spectrum provided by this invention;

[0038] Figure 6 The Fe EDS Mapping spectrum provided by this invention;

[0039] Figure 7 The CEDS Mapping spectrum provided by this invention.

[0040] Figure labeling: 1-Alloyed nano-silicon core; 2-Carbon coating layer; 1a-Silicon core; 1b-Silicon-metal composite; 3-Polymer layer.

[0041] The accompanying drawings have illustrated specific embodiments of the invention, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0043] In the field of energy storage, silicon-carbon composite materials are a type of lithium-ion battery anode material with silicon as the active component and carbon as the conductive and structural support component, and have become an important development direction for high-energy-density lithium-ion battery anode materials.

[0044] However, existing silicon-carbon composite materials still have certain limitations. During charge and discharge, silicon materials undergo significant volume changes, which can easily lead to particle breakage, structural instability, and reduced utilization of active materials. Simultaneously, interfacial side reactions easily occur when the material surface comes into contact with the electrolyte, affecting interfacial stability and long-term cycle performance. Furthermore, existing silicon-carbon materials still struggle to achieve an effective balance between conductivity, structural stability, and interfacial stability, leaving room for further improvement in capacity retention and cycle life.

[0045] Based on this, the present invention proposes a composite silicon-carbon material. This material constructs a silicon-metal composite on the surface of nano-silicon particles and further forms a carbon coating layer on its outer side, creating a multi-functional composite structure. The silicon-metal composite improves the structural stability and conductivity of the particle surface, while the carbon coating layer constructs a continuous conductive network and provides protection and buffering for the particles. This effectively mitigates volume changes during charge and discharge processes and reduces interfacial side reactions while maintaining the high specific capacity of the silicon material, thereby improving the material's cycle stability and capacity retention.

[0046] In a first aspect, the present invention provides a composite silicon-carbon material, such as... Figure 1 The diagram shown is a cross-sectional view of the composite silicon-carbon material provided in an embodiment of the present invention. It includes an alloyed nano-silicon core 1 and a carbon coating layer 2 covering at least a portion of the surface of the alloyed nano-silicon core 1; wherein,

[0047] The average particle size of the alloyed nano-silicon core 1 is 30-80 nm;

[0048] The alloyed nano-silicon core 1 includes a silicon core 1a and a silicon-metal composite 1b surrounding the surface of the silicon core 1a, the thickness of which is 8-12 nm.

[0049] The present invention uses alloyed nano-silicon core 1 as active material, wherein the average particle size of nano-silicon is controlled to be 30-80nm, which enables lithium ions to be inserted and extracted more quickly, while reducing stress concentration caused by volume change inside the particles, thereby reducing the tendency of particles to crack and pulverize.

[0050] Furthermore, a silicon-metal composite 1b with a thickness of 8-12 nm is formed on the surface of the silicon core 1a, so that the metal elements are mainly distributed in the surface region of the particles, forming a composite structure with silicon. Since the silicon-metal composite 1b has high mechanical stability and electrical conductivity, it can provide support for the surface of silicon particles, disperse the local stress caused by silicon volume changes during charging and discharging, reduce the risk of surface structural instability, and improve the electron transport capability of the particle surface.

[0051] The thickness of the silicon-metal composite 1b is controlled at 8-12 nm, so that the alloying region is mainly concentrated on the particle surface, while the particle interior still maintains a high proportion of silicon active phase. On the one hand, surface alloying can enhance the structural stability of the outer layer of the particle; on the other hand, it can avoid excessive diffusion of metal elements into the particle interior, which would reduce the proportion of silicon active material. This maintains a high lithium storage capacity while taking into account the mechanical stability and conductivity of the particle.

[0052] Coating the alloyed nano-silicon core 1 with a carbon coating layer 2 enables the construction of continuous electron transport pathways between particles, improving the overall conductivity of the composite material. Simultaneously, it isolates the active particles from the external electrolyte to a certain extent, reducing direct exposure of the particle surface. Furthermore, the carbon coating layer 2 provides a buffer against volume changes in the silicon particles during charging and discharging, reducing interparticle contact failure and structural damage.

[0053] This invention constructs a multi-level composite structure by means of a nano-silicon core, a silicon-metal composite 1b, and a carbon coating layer 2. The nano-silicon core provides a high lithium storage capacity, the silicon-metal composite 1b enhances the structural stability and electron transport capability of the particle surface, and the carbon coating layer 2 further constructs a conductive network and provides buffering and protection for the particles. While maintaining the high specific capacity advantage of silicon materials, this invention effectively improves the structural stability, capacity retention, cycle life, and rate performance of the composite material.

[0054] In one possible embodiment, the thickness of the carbon coating layer 2 is 2-10 nm.

[0055] In this embodiment, since the present invention adopts a surface alloying rather than an integral alloying structure, the particles already have high mechanical stability. Therefore, the carbon coating layer 2 does not need to undertake the main structural support function, but rather undertakes the conductive connection and interface buffering function. Thus, a synergistic optimization of high capacity and high cycle stability can be achieved by using an ultrathin coating layer of 2-10 nm.

[0056] This thickness, on the one hand, can form a continuous conductive network on the surface of the alloyed nano-silicon core 1, improve the electron transport efficiency between particles, and provide a certain buffer and protection for the silicon particles; on the other hand, it can reduce the problem of reduced active silicon content and increased lithium ion diffusion path caused by excessive carbon layer thickness, thus balancing the capacity utilization and rate performance of the material.

[0057] In one possible embodiment, a polymer layer 3 is further included, which is coated on at least a portion of the outer surface of the carbon coating layer 2, and the polymer layer 3 has a thickness of 1-10 nm.

[0058] In this embodiment, after further constructing a polymer layer 3 on the outside of the carbon coating layer 2, a continuous interface protective layer can be formed, reducing interfacial side reactions caused by direct contact between the carbon coating layer 2 and the electrolyte. Simultaneously, the polymer layer 3 possesses a certain degree of flexibility, allowing it to deform with the volume change of the silicon particles during charging and discharging, alleviating interfacial stress concentration, improving the integrity of the coating layer, and thus further maintaining the structural stability of the alloyed nano-silicon core 1 and the carbon coating layer 2.

[0059] Preferably, the polymer layer 3 has a thickness of 1-10 nm, which can achieve effective interface protection while maintaining rapid lithium ion transport. It forms a synergistic effect with the inner silicon-metal composite 1b and carbon coating layer 2, and is more suitable for the nanoscale multilayer composite structure constructed in this invention.

[0060] In one possible embodiment, the silicon-metal composite 1b includes a metal element, which includes at least one of Fe, Cu, Ni, Co, Ti, V, and Cr.

[0061] In this embodiment, all of the above-mentioned metal elements have the ability to form stable silicides or silicon-based metal composite phases with silicon, with Fe, Cu, and Ni being preferred. The formed silicon-metal composite 1b can disperse the local stress caused by the volume change of silicon particles during charging and discharging, reducing the risk of particle surface cracking and pulverization; at the same time, the silicon-based metal composite phase formed by the above-mentioned metal elements has good electron transport performance, which can improve the electron transport capability of the particle surface and promote electrochemical reactions.

[0062] In one possible embodiment, the carbon coating layer 2 is an amorphous carbon layer.

[0063] In this embodiment, since the present invention uses alloyed nano-silicon cores 1 with an average particle size of 30-80 nm, the particle size is small and a silicon-metal composite 1b has been formed on the surface. Therefore, in addition to undertaking the role of electron transport, the carbon coating layer 2 also needs to adapt to the volume change of the nano-silicon particles during the charging and discharging process.

[0064] Amorphous carbon has a high degree of structural disorder and abundant defect sites. When it is coated on the surface of silicon-metal composite 1b, it can form a continuous and uniform conductive layer and has a certain degree of flexibility, which can adapt to changes in particle volume.

[0065] Meanwhile, amorphous carbon can usually be formed at lower temperatures, which helps to avoid the growth of nano-silicon particles, changes in silicon lattice, or the impact on the surface silicon-metal composite 1b structure during high-temperature graphitization, thereby maintaining the surface alloying structure constructed in this invention.

[0066] In one possible embodiment, polymer layer 3 includes at least one of carboxymethyl cellulose, polyvinylidene fluoride, and sodium alginate, and has a weight-average molecular weight of 80,000-120,000 g / mol.

[0067] In this embodiment, since the mechanical stability of the particle surface has been improved by the silicon-metal composite 1b and an electron transport network has been established by the ultrathin carbon coating layer 2, the polymer layer 3 does not need to undertake the main structural support function, but mainly plays the role of interface protection and stress buffering.

[0068] All of the above polymers can be adsorbed on the surface of the carbon coating layer 2 to form a continuous and uniform polymer protective layer, which can further reduce the direct contact between the carbon coating layer 2 and the electrolyte, reduce interfacial side reactions, and improve interfacial stability; at the same time, they can undergo synergistic deformation with the volume change of the alloyed nano-silicon particles during the charging and discharging process, thereby relieving the local stress on the particle surface.

[0069] It should be noted that the carbon coating layer and polymer layer of the present invention can be distributed continuously or discontinuously on at least part of the surface of the corresponding particles, and it is not required that the coating layer completely covers the entire outer surface of the particles.

[0070] The coating thickness in this invention refers to the average thickness measured using a transmission electron microscope on the area containing the coating layer, i.e., the average thickness of the actual coated area. The coating thickness may vary to some extent between different particles or at different locations on the same particle.

[0071] Figure 1 This diagram is only used to illustrate the relative positions of the components of the composite silicon-carbon material. For ease of illustration, the carbon coating layer 2 and polymer layer 3 are depicted as a continuous layered structure, but this does not mean that the carbon coating layer 2 and polymer layer 3 must completely cover the entire surface of the corresponding particles.

[0072] The average particle size of this invention refers to the average particle size of the alloyed silicon nanonuclei, excluding the thickness of the carbon or polymer layer on their surface. The outer boundary of the alloyed silicon nanonuclei is determined based on TEM images combined with energy dispersive spectroscopy elemental surface scanning or line scanning.

[0073] In a second aspect, the present invention provides a method for preparing any of the composite silicon-carbon materials in the first aspect, wherein the temperature of the plasma arc region is controlled at 1800-2500℃, and a silicon source is continuously introduced during continuous operation for 10-15 minutes to perform nano-sizing treatment, thereby forming silicon core raw materials;

[0074] The raw material system, including silicon core material and metal source, is alloyed under the condition of plasma arc temperature of 1800-2500℃ for 15-60 minutes of continuous operation to form alloyed nano silicon core.

[0075] Alloyed nano-silicon cores and carbon sources are subjected to carbon coating treatment at 450-550℃ for 10-12 hours to obtain composite silicon-carbon materials.

[0076] In this invention, by controlling the time window for the nucleation of nano-silicon and the introduction of metal, the silicon source is first vaporized, nucleated, and grown in a high-temperature environment of 1800-2500℃, forming active nano-silicon nuclei in the 10-15 min stage; then, the metal source is introduced in the 15-60 min stage. Since the surface of the nano-silicon particles is still in a highly active state at this time, metal atoms can diffuse, embed, and undergo local lattice reconstruction on the particle surface, forming a stable silicon-metal composite region with silicon atoms, rather than simply covering the surface of silicon particles, thereby forming a gradient structure with a highly active silicon phase inside and a silicon-metal composite outside.

[0077] Furthermore, rapid quenching immediately after leaving the high-temperature zone can reduce the risk of further particle growth and excessive diffusion of metal elements into the interior under high-temperature conditions, thus ensuring that the silicon-metal composite region is stably retained on the surface of the nano-silicon particles.

[0078] Compared to existing methods that first prepare silicon particles and then coat them with metal, this invention achieves precise control over the spatial distribution of metal elements by synergistically regulating the reaction stage and the timing of metal introduction. This maintains the high capacity characteristics of silicon materials while improving the stability of particle structure and the strength of interfacial bonding.

[0079] In the carbon coating process, 450-500℃ for 10-12 hours is sufficient to meet the requirements for carbon layer formation, while avoiding the growth of nano-silicon particles, changes in the silicon lattice structure, or further diffusion of the surface silicon-metal composite 1b caused by high temperatures, thus maintaining the structural integrity of the alloyed nano-silicon core 1. The formed carbon coating layer 2 can construct a continuous electron transport pathway and provide buffering and protection for the particles, further improving the cycle stability and capacity retention of the composite material.

[0080] In this invention, a metal source can be introduced during a specific reaction stage of the formation of nano-silicon particles in the process of plasma preparation. During the continuous growth of nano-silicon particles, the metal elements form a surface alloying structure to obtain an alloyed nano-silicon core 1.

[0081] Compared to overall alloying, this method allows the metal elements to be mainly distributed on the outer layer of the particles, while maintaining a high proportion of silicon active phase inside the particles, thus achieving a balance between high lithium storage capacity, structural stability, and conductivity. The plasma method introduces the metal source in situ during preparation, eliminating the need for a separate surface modification step. This allows for simultaneous preparation of nano-silicon and surface alloying, improving coating uniformity and process continuity while reducing preparation costs.

[0082] In one specific embodiment, the alloying treatment can be achieved by one or more of the following methods: plasma heat treatment, induction heating, high-temperature sintering, vapor deposition, chemical vapor deposition (CVD), physical vapor deposition (PVD), fluidized bed heat treatment, spray pyrolysis, or rapid heat treatment.

[0083] In one specific embodiment, the carbon coating treatment can be achieved by one or more of the following methods: mechanical mixing carbonization, chemical vapor deposition (CVD), spray coating, fluidized bed coating, rotary kiln carbonization, roller furnace carbonization, pusher furnace carbonization, or tube furnace pyrolysis.

[0084] In one specific embodiment, the silicon source can be selected from at least one of silane, trichlorosilane, silicon tetrachloride, dichlorosilane, polycrystalline silicon, industrial silicon, and metallic silicon powder.

[0085] Preferably, after the alloyed nano-silicon core 1 is thoroughly mixed with the carbon source, it is subjected to low-temperature pyrolysis carbonization under a protective atmosphere, so that the carbon source is pyrolyzed on the particle surface and forms a continuous amorphous carbon coating layer 2; wherein, the carbon source can be selected from resin, asphalt, etc.

[0086] It should be noted that in this invention, 10-15 min and 15-60 min are the operating times for the plasma reactor to perform the corresponding continuous feeding operation, and the temperature of the plasma arc region of the plasma reactor is controlled at 1800-2500℃. The silicon source, silicon core material, and metal source pass through the plasma arc region for a short time, thereby inhibiting the continuous growth of particles and the excessive diffusion of metal elements into the silicon particles.

[0087] In one possible embodiment, after carbon coating treatment, the product of carbon coating treatment is further subjected to extrusion mixing with a polymer solution; and then dried at 100-110°C for 8-12 hours to obtain a composite silicon-carbon material.

[0088] In this embodiment, some defect sites may still exist on the surface of the carbon layer after carbon coating. Further extrusion mixing with a polymer solution allows the polymer to adhere uniformly to the surface of the carbon coating layer 2 under mechanical action, further reducing the surface free energy of the particles, decreasing particle agglomeration, and forming a continuous and stable polymer protective layer. Furthermore, drying the coated product at 100-110°C for 8-12 hours slowly removes the solvent from the polymer solution, thereby forming a uniform, continuous, and stable polymer coating layer.

[0089] In one specific embodiment, the carbon-coated product and the polymer solution can be added to a mechanical fusion machine. Under the mechanical shearing, particle collision and compaction action formed between the high-speed rotating impeller and the stator and rotor, the polymer solution uniformly wets the particle surface and is uniformly adsorbed on the surface of the carbon coating layer 2 during the continuous rolling, dispersion and mutual friction of the particles.

[0090] The obtained powder was then placed in a vacuum drying oven and treated at 100°C for 12 h to allow the solvent in the polymer solution to evaporate and promote further spreading of the polymer chain segments, ultimately forming a stable polymer protective layer on the outside of the carbon coating layer.

[0091] In one possible embodiment, the mass ratio of the carbon-coated product to the polymer solution is (95-100):2, and the polymer content in the polymer solution is 2-2.5 wt.%.

[0092] In this embodiment, the polymer is mainly used to locally modify defect sites, high surface energy regions, and particle contact sites on the surface of the carbon coating layer. The polymer solution is dispersed on the surface of the carbon-coated powder during mechanical fusion. After drying to remove the solvent, a polymer-coated region is formed on at least a portion of the outer surface of the carbon coating layer. This polymer-coated region can reduce the direct contact between some active sites and the electrolyte, and provide a certain degree of flexible buffering at the particle contact sites.

[0093] In some embodiments, the plasma treatment employs a thermal plasma reactor with a plasma power of 30-80 kW, an absolute pressure of 50-100 kPa within the reactor, and a high-temperature plasma zone temperature of 1800-2500℃. Argon is used as the carrier gas with a flow rate of 20-60 L / min; the feed rate of the silicon source is 2-10 g / min based on silicon elemental mass, and the feed rate of the metal source is adjusted according to a silicon to metal elemental mass ratio of (8-10):1.

[0094] In some embodiments, the actual residence time of the material in the high-temperature plasma zone is 0.05-1 s. A quenching zone is set downstream of the high-temperature zone of the reactor, and argon or nitrogen gas at a flow rate of 20-80 L / min is introduced into the quenching zone as a quenching gas.

[0095] In one possible embodiment, after the carbon coating treatment, the product of the carbon coating treatment is further subjected to sieve depolymerization treatment and then extrusion mixing treatment.

[0096] In this embodiment, due to the high specific surface area and surface energy of the nano-silicon particles, during the carbon coating process, the particles are easily affected by pyrolysis and carbonization, as well as interparticle contact, leading to the formation of soft aggregates bound by van der Waals forces or capillary forces. Therefore, adding a sieving and depolymerization treatment after carbon coating can effectively break up the soft aggregates, allowing the carbon-coated particles to redisperse, providing more effective interfaces for subsequent uniform polymer adsorption, and improving the consistency of distribution.

[0097] In one specific embodiment, the deagglomeration treatment includes one or more of the following: vibrating sieving, airflow sieving, ultrasonic deagglomeration, mechanical deagglomeration, high-speed shear deagglomeration, airflow milling deagglomeration, or ball milling deagglomeration. Preferably, a combination of vibrating sieving and mechanical deagglomeration is used. Larger agglomerated particles are first removed, and then soft agglomerates are broken up using mechanical collision and shearing. This improves particle dispersibility while maintaining the integrity of the carbon coating layer 2. The undersize material can directly enter the subsequent extrusion and mixing process, while the oversize material is deagglomerated, re-sieved, and returned to subsequent processes, achieving powder recycling.

[0098] In one possible embodiment, the mass ratio of silicon in the silicon source to metal in the metal source is (8-10):1.

[0099] In this embodiment, since the present invention only constructs a silicon-metal composite 1b with a thickness of 8-12 nm on the surface of nano-silicon particles, a large amount of metal source is not required to participate in the reaction. Controlling the mass ratio of silicon to metal within the above range is more conducive to forming the surface gradient alloying structure required by the present invention.

[0100] In one possible embodiment, the mass of the carbon source is 2-3% of the mass of the alloyed nano-silicon core 1.

[0101] In this embodiment, the carbon coating layer 2 mainly serves as a conductive connection and interface protection, therefore a high coating amount is not required. By controlling the amount of carbon source added to 2-3% of the mass of the alloyed nano-silicon core 1, a continuous amorphous carbon coating layer 2 with a thickness of about 2-10 nm can be formed during the pyrolysis carbonization process. This ensures electron transport performance and interface protection while minimizing the impact of inactive carbon components on the specific capacity of the material.

[0102] Thirdly, the present invention provides an electrode comprising any of the composite silicon-carbon materials of the first aspect of the present invention, or a composite silicon-carbon material obtained by any of the methods of the second aspect of the present invention.

[0103] Since the composite silicon-carbon material provided by this invention uses an alloyed nano-silicon core 1, a carbon coating layer 2, and an optional polymer layer 3 to construct a multi-layer gradient structure, it can form a more stable conductive network and particle structure when used as a negative electrode active material to prepare an electrode sheet.

[0104] During charging and discharging, the alloyed nano-silicon core 1 can improve the stability of the particle structure, the carbon coating layer 2 ensures the rapid transfer of electrons between particles, and the polymer layer 3 further reduces the interfacial side reactions between particles and electrolyte. This can slow down the expansion, pulverization and conductive network failure of the electrode caused by silicon volume changes, and improve the compaction density, cycle stability and rate performance of the electrode.

[0105] The electrode of the present invention specifically includes a current collector and an active layer formed of silicon-carbon material provided by the present invention disposed on the surface of the current collector.

[0106] In one specific embodiment, the electrode sheet can be prepared as follows: the composite silicon-carbon material provided by the present invention is used as the negative electrode active material, mixed with a conductive agent, a binder, and a dispersion medium, and dispersed by stirring to form a uniform slurry; then the slurry is uniformly coated on the surface of the current collector, and the electrode sheet is obtained by sequentially performing drying, rolling, and slitting processes. The conductive agent includes one or more of conductive carbon black, acetylene black, Super P, conductive graphite, carbon nanotubes, and graphene; the binder includes one or more of polyvinylidene fluoride, carboxymethyl cellulose, and styrene-butadiene rubber; the dispersion medium includes one of deionized water and N-methylpyrrolidone; the current collector is preferably copper foil, but other conductive current collectors suitable for the negative electrode can also be used.

[0107] Fourthly, the present invention provides a battery including the electrode sheet of the third aspect of the present invention.

[0108] The electrode provided by this invention has excellent structural stability and electrochemical performance. Therefore, the battery prepared by this invention can effectively reduce negative electrode polarization and interface impedance growth during cycling, improve lithium-ion insertion / extraction efficiency, and improve battery cycle life and rate performance.

[0109] Meanwhile, composite silicon-carbon materials can fully leverage the high specific capacity advantage of silicon materials, improving the capacity retention rate and charge-discharge stability of the battery after long-term cycling while maintaining a high energy density, thus enabling the battery to have both high energy density, power density and cycle life.

[0110] In one specific embodiment, the battery can be prepared as follows: The electrode sheet of the third aspect of this invention is assembled with a positive electrode sheet, a separator, and an electrolyte to form a battery cell. The cell is then subjected to winding or stacking, encapsulation, electrolyte injection, static immersion, formation, and capacity testing to obtain the battery. The positive electrode sheet can be prepared using positive active materials such as lithium iron phosphate, lithium manganese iron phosphate, ternary materials, lithium cobalt oxide, and lithium manganese oxide. The separator includes one or more of polyethylene separators, polypropylene separators, polyolefin composite separators, or ceramic-coated separators. The electrolyte includes lithium salts, organic solvents, and functional additives. The lithium salts include one or more of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, and other similar materials. The organic solvents include one or more of ethylene carbonate, dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate, and fluoroethylene carbonate. The functional additives include one or more of vinyl carbonate, propane sulfonate lactone, and 1,3-propane sulfonate lactone derivatives.

[0111] In this invention, the electrode sheet can be prepared using existing lithium-ion battery electrode sheet manufacturing processes; the battery can be manufactured in different structural forms such as cylindrical batteries, prismatic batteries, pouch batteries, stacked batteries, or wound batteries. This invention mainly focuses on improving the negative electrode active material, and therefore is not limited by the electrode sheet manufacturing process, battery packaging form, or battery structure.

[0112] In one possible embodiment, the battery is a solid-state battery, which includes a solid electrolyte layer. The solid electrolyte material in the solid electrolyte layer includes one of lithium-sulfur-phosphorus-chloride solid electrolyte, lithium sulfide-phosphorus pentasulfide composite sulfide solid electrolyte, and germanium-doped lithium-phosphorus-sulfide solid electrolyte.

[0113] In this embodiment, the sulfide solid electrolyte exhibits high lithium-ion transport capability and low interfacial contact impedance, meeting the requirements of high-capacity silicon-based anode materials for rapid lithium-ion transport. However, silicon anodes undergo significant volume changes during charge and discharge, which can easily lead to electrode particle breakage, electrode structural instability, and a decrease in the contact area with the solid electrolyte.

[0114] This invention constructs an alloyed nano-silicon core structure, distributing silicon-metal composite regions on the outer side of the silicon core. The metal component enhances the surface structural strength and alleviates the mechanical stress generated during silicon lithium intercalation. Simultaneously, the carbon coating provides a continuous electron transport channel and isolates the silicon active surface from direct contact with the sulfide solid electrolyte, reducing the probability of interfacial side reactions. Therefore, the composite silicon-carbon material of this invention can form a stable solid-solid interface with the sulfide solid electrolyte, which is beneficial for improving the cycle stability and capacity retention of solid-state batteries.

[0115] In one possible embodiment, the composite silicon-carbon material can be used to prepare the negative electrode of a solid-state battery. The solid-state battery also includes a positive electrode, a solid electrolyte layer, and a current collector. The positive electrode may include a positive electrode active material, a conductive agent, and a binder. The positive electrode active material includes, but is not limited to, at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, and lithium cobalt oxide.

[0116] Fifthly, the present invention provides an electrical device including the battery of the fourth aspect of the present invention.

[0117] Because the battery of the present invention has high energy density, excellent cycle stability and rate performance, it can meet the usage requirements of high energy density and long life application scenarios.

[0118] For example, electrical equipment includes, but is not limited to, new energy vehicles, hybrid vehicles, two-wheeled electric vehicles, power tools, drones, robots, energy storage systems, communication base station energy storage equipment, portable energy storage power supplies, laptops, tablets, smartphones, smart wearable devices, digital products, medical equipment, industrial equipment, and aerospace power supply systems.

[0119] The present invention will be described in more detail below through specific embodiments.

[0120] Example 1

[0121] This embodiment is used to prepare the composite silicon-carbon material provided by the present invention.

[0122] The temperature of the plasma arc region in the plasma reactor was controlled at 2500℃. Silane was continuously introduced during 10 min of continuous operation to perform nano-sizing. After leaving the plasma arc region, the silicon nucleus material was formed by rapid cooling. Ni powder was then added as a metal source, and alloying was performed at 2500℃ for 15 min to obtain alloyed nano-silicon nuclei 1, in which the mass ratio of silicon to metal was 9:1, and the thickness of the silicon-metal composite was approximately 10 nm.

[0123] Phenolic resin was added as a carbon source to the obtained alloyed nano-silicon core 1. The amount of carbon source added was 2% of the mass of the alloyed nano-silicon core. After thorough mixing, the mixture was placed in a box furnace and kept at 550 °C for 12 h under nitrogen protection to allow the phenolic resin to pyrolyze and form an amorphous carbon coating layer, thus obtaining a composite silicon-carbon material with a carbon coating layer thickness of about 5 nm.

[0124] Example 2

[0125] This embodiment is used to verify the formation of surface alloying structures by different metal elements.

[0126] This embodiment is basically the same as Embodiment 1, except that the metal source is Fe powder.

[0127] Example 3

[0128] This embodiment is used to verify the optimization of carbon coating thickness.

[0129] This embodiment is basically the same as Embodiment 1, except that the silicon-metal composite is alloyed according to a silicon-to-metal mass ratio of 8:1, and the thickness of the silicon-metal composite is about 12 nm.

[0130] Phenolic resin was then added as a carbon source, with the amount of carbon source added being 3% of the mass of the alloyed nano-silicon core. The mixture was then heated at 550 °C for 12 h to perform carbonization treatment, forming an amorphous carbon coating layer with a thickness of about 10 nm.

[0131] Example 4

[0132] This embodiment is used to verify the polymer coating layer.

[0133] The composite silicon-carbon material obtained in Example 2 was used as a raw material and mechanically fused with an aqueous carboxymethyl cellulose solution in a fusion machine. The mass ratio of the composite silicon-carbon material to the aqueous carboxymethyl cellulose solution was 98:2, and the mass fraction of carboxymethyl cellulose in the aqueous carboxymethyl cellulose solution was 2 wt.%. The fusion machine rotated at 1500 rpm, and the processing time was 20 min.

[0134] Subsequently, the obtained powder was placed in a vacuum drying oven and dried at 105°C for 10 hours to obtain a composite silicon-carbon material with a polymer layer. Transmission electron microscopy revealed that the average thickness of the carboxymethyl cellulose layer in the actual coated area was approximately 3 nm.

[0135] Example 5

[0136] This embodiment is basically the same as embodiment 4, except that the polymer used is sodium alginate, which ultimately forms a polymer layer with a thickness of about 5 nm.

[0137] Example 6

[0138] This embodiment is basically the same as embodiment 4, except that the composite silicon-carbon material obtained in embodiment 2 is subjected to sieve depolymerization treatment before polymer coating treatment.

[0139] Specifically, the material was first sieved using a 500-mesh vibrating screen to collect the undersize material. The oversize material was then added to a mechanical depolymerizer and depolymerized at 3000 rpm for 10 minutes, followed by sieving again. This depolymerization and sieving process was repeated until the cumulative mass of the undersize material accounted for more than 99% of the total mass of the raw material powder. The undersize materials from each sieve were combined, and then coated with carboxymethyl cellulose and vacuum dried according to the method in Example 4 to obtain the composite silicon-carbon material.

[0140] Example 7

[0141] This embodiment is basically the same as Embodiment 1, except that a carbon coating layer is formed by vapor deposition and a polymer layer is further formed.

[0142] Specifically, the alloyed nano-silicon cores obtained in Example 1 were placed in a rotary tube furnace and deposited at 500°C by introducing an acetylene / nitrogen mixture with a volume fraction of 0.8%. Subsequently, the resulting powder was mixed with a 2 wt.% carboxymethyl cellulose aqueous solution at a mass ratio of 100:30, spray-dried, and then vacuum-dried at 105°C for 10 hours. The average thicknesses of the carbon coating layer and the carboxymethyl cellulose layer in the actual coating area were 2.1 nm and 1.1 nm, respectively.

[0143] Example 8

[0144] This embodiment is basically the same as Embodiment 7, except that the volume fraction of acetylene in the acetylene / nitrogen mixture is 2.0%, the vapor deposition temperature is 550℃, and the deposition time is 12h; and a polyvinylidene fluoride N-methylpyrrolidone solution with a mass fraction of 8% is used for polymer coating, the mass ratio of the resulting carbon-coated powder to the polyvinylidene fluoride solution is 100:60, the vacuum drying conditions are 110℃ and 12h, and the average thicknesses of the carbon coating layer and the polyvinylidene fluoride layer in the actual coating area are 9.8nm and 9.6nm, respectively.

[0145] Comparative Example 1: Integral Silicon-Metal Alloy Structure

[0146] Unlike the silicon-metal composite structure surrounding the silicon core in the embodiments, this comparative example uses an integral alloying method to prepare the silicon-based material. The silicon source and metal source are mixed and then subjected to high-temperature alloying treatment to ensure uniform distribution of metal elements within and on the surface of the silicon particles, forming an integral silicon-metal alloy structure. Subsequently, carbon coating treatment is performed according to the method of Example 1 to obtain the composite silicon-carbon material of Comparative Example 1.

[0147] Comparative Example 2: Non-alloyed metal deposition structure

[0148] This comparative example uses surface metal deposition to prepare silicon-based materials. First, nano-silicon particles with an average particle size of 30-80 nm are prepared. Then, a metal source is introduced onto the surface of these particles, causing metal elements to deposit onto the surface of the nano-silicon particles, forming a non-alloyed metal coating layer. Subsequently, carbon coating treatment is performed according to the method of Example 1 to obtain the composite silicon-carbon material of Comparative Example 2.

[0149] Test Case 1 (SEM Analysis)

[0150] The material obtained in Example 4 was observed using a scanning electron microscope (SEM).

[0151] like Figure 2 The image shown is a SEM characterization spectrum provided by the present invention. The obtained material is composed of nano-sized particles with an overall spherical structure and a relatively uniform particle size distribution. No obvious large-sized blocky agglomerates were observed, indicating that the preparation method can obtain a nanocomposite powder structure with good dispersibility.

[0152] Test Example 2 (TEM and EDS Analysis)

[0153] The microstructure of the composite silicon-carbon material obtained in Example 4 was observed using transmission electron microscopy (TEM) and analyzed using EDS elemental surface scanning.

[0154] like Figure 3The image shown is a TEM characterization spectrum provided by the present invention. The composite silicon-carbon material particles exhibit obvious core-shell structure characteristics. There is an electronic contrast difference between the central region and the peripheral region of the particles. The periphery has a continuous coating layer, and the interface between the coating layer and the particle body is tightly bonded without obvious voids.

[0155] like Figure 4 The EDS spectrum provided by this invention shows that the material mainly contains Si, Fe and C elements.

[0156] like Figure 5 The image shown is a Si EDS Mapping spectrum provided by this invention, as follows: Figure 6 The image shown is a FeEDS mapping spectrum provided by this invention. Figure 7 The image shown is a CEDS Mapping spectrum provided by this invention.

[0157] The surface distribution map of Si element shows that silicon covers the entire particle region, mainly concentrated in the main body of the particle, indicating that the obtained material has a nano-silicon structure as its core component. The surface distribution map of Fe element shows that the Fe element signal has a high degree of overlap with the Si element distribution area, and no obvious independent iron particle aggregation phenomenon was observed, indicating that the metal element is not simply physically mixed or deposited on the outside of the particle, but rather forms a stable silicon-metal composite region with the silicon component. The surface distribution map of C element shows that carbon element is mainly distributed in the peripheral region of the particle and forms a continuous distribution along the particle outline, indicating that the carbon source forms a carbon coating layer on the surface of the alloyed nano-silicon core after heat treatment.

[0158] The above results demonstrate that the present invention has successfully constructed a composite silicon-carbon material consisting of a silicon-based core, a silicon-metal composite region, and an outer carbon coating structure.

[0159] Test Example 3 (Electrochemical Performance Test)

[0160] The composite silicon-carbon materials obtained in Examples 1-8 and Comparative Examples 1-2 were used to prepare negative electrode sheets, which were then combined with high-nickel ternary dry-process electrode sheets and sulfide electrolyte membranes. After stacking and isostatic pressing, they were packaged into 2cm×2cm solid-state soft-pack batteries, and the following electrochemical performance tests were conducted.

[0161] The tests included 0.1C discharge capacity, initial charge-discharge efficiency, 0.33C, 0.5C, and 1C rate performance, and 100-cycle performance.

[0162] Table 1. Comparison of electrochemical performance between the examples and comparative examples

[0163] serial number 0.1C discharge specific capacity (mAh / g) First charge / discharge efficiency 0.33c rate performance 0.5c rate performance 1c rate performance 100-cycle performance Example 1 185 80% 88% 80% 75% 92% Example 2 186 82% 88% 82% 75% 94% Example 3 183 78% 89% 82% 77% 90% Example 4 189 82% 87% 80% 76% 98% Example 5 188 83% 87% 81% 75% 98% Example 6 190 82% 88% 82% 77% 97% Example 7 190 82% 89% 82% 76% 93% Example 8 184 84% 87% 81% 74% 98% Comparative Example 1 180 80% 86% 79% 74% 95% Comparative Example 2 185 81% 86% 80% 74% 94%

[0164] As shown in Table 1, the embodiments of the present invention exhibit good discharge specific capacity, rate performance, and cycle stability. Examples 1 and 2 demonstrate that the surface alloying structure is applicable to different metal systems; in Example 3, the capacity, initial efficiency, and cycle performance decreased after the carbon coating layer was thickened, indicating that the carbon layer thickness needs to be reasonably controlled.

[0165] Compared with Example 2, the capacity retention rate after 100 cycles increased from 94% to 98% after adding a carboxymethyl cellulose layer in Example 4; the capacity retention rate after using sodium alginate in Example 5 also reached 98%, indicating that the polymer layer can improve the interfacial stability.

[0166] Compared to Example 4, Example 6 showed improved capacity and rate performance after sieve depolymerization, indicating that reducing agglomeration is beneficial for improving material dispersibility. Examples 7 and 8 further demonstrate that good electrochemical performance can be achieved across various thickness ranges of both the carbon coating and polymer layer. Compared to the comparative examples, the examples optimized through coating and sieve depolymerization exhibit superior overall performance.

[0167] Finally, it should be noted that other embodiments of the invention will readily conceive of those skilled in the art upon consideration of the invention disclosed in the specification and in practice. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings. Various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A composite silicon-carbon material, characterized in that, It includes an alloyed silicon nanonucleus and a carbon coating layer covering at least a portion of the surface of the alloyed silicon nanonucleus; wherein, The average particle size of the alloyed nano-silicon cores is 30-80 nm. The alloyed nano-silicon core includes a silicon core and a silicon-metal composite surrounding the surface of the silicon core, wherein the thickness of the silicon-metal composite is 8-12 nm.

2. The material according to claim 1, characterized in that, It also includes a polymer layer covering at least a portion of the outer surface of the carbon coating layer, the polymer layer having a thickness of 1-10 nm; and / or, the carbon coating layer having a thickness of 2-10 nm.

3. The material according to claim 2, characterized in that, The silicon-metal composite includes a metallic element, which includes at least one selected from Fe, Cu, Ni, Co, Ti, V, and Cr; and / or, The carbon coating layer is an amorphous carbon layer; and / or, The polymer layer includes at least one of carboxymethyl cellulose, polyvinylidene fluoride, and sodium alginate, and has a weight-average molecular weight of 80,000-120,000 g / mol.

4. A method for preparing the composite silicon-carbon material according to any one of claims 1-3, characterized in that, The temperature of the plasma arc region is controlled at 1800-2500℃, and a silicon source is continuously introduced during continuous operation for 10-15 minutes to perform nano-sizing treatment and form silicon core raw materials. The raw material system, including the silicon core material and the metal source, is alloyed under the condition that the plasma arc temperature is 1800-2500℃ for 15-60 minutes during continuous operation to form the alloyed nano silicon core. The alloyed nano-silicon core and carbon source are subjected to carbon coating treatment at 450-550℃ for 10-12 hours to obtain the composite silicon-carbon material.

5. The method according to claim 4, characterized in that, After the carbon coating treatment, the product of the carbon coating treatment is further subjected to extrusion mixing with a polymer solution; and then dried at 100-110°C for 8-12 hours to obtain the composite silicon-carbon material.

6. The method according to claim 5, characterized in that, The mass ratio of the carbon-coated product to the polymer solution is (95-100):2, and the polymer content in the polymer solution is 2-2.5 wt.%.

7. The method according to claim 6, characterized in that, The mass ratio of silicon in the silicon source to metal in the metal source is (8-10):

1.

8. The method according to claim 7, characterized in that, After the carbon coating treatment, the product of the carbon coating treatment is further subjected to sieve depolymerization treatment, followed by the extrusion mixing treatment.

9. The method according to any one of claims 4-8, characterized in that, The mass of the carbon source is 2-3% of the mass of the alloyed nano-silicon core.

10. An electrode sheet, characterized in that, Includes the composite silicon-carbon material according to any one of claims 1-3, or the composite silicon-carbon material obtained by the method according to any one of claims 4-9.

11. A battery, characterized in that, Includes the electrode as described in claim 10.

12. The battery according to claim 11, characterized in that, The battery is a solid-state battery, which includes a solid electrolyte layer. The solid electrolyte material in the solid electrolyte layer includes one of lithium-sulfur-phosphorus-chloride solid electrolyte, lithium sulfide-phosphorus pentasulfide composite sulfide solid electrolyte, and germanium-doped lithium-phosphorus-sulfide solid electrolyte.

13. An electrical appliance, characterized in that, Includes the battery as described in claim 11 or 12.